English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

assume (ab)^2 = a^2 b^2
but (ab)^2 = abab
so we have that abab = a^2b^2
multiply from the left by a^{-1} and from the right by b^{-1} both sides of the equality,
then ba = ab which means that G is abelian .

2007-02-02 13:16:58 · answer #1 · answered by tablecloth 1 · 2 0

(ab)^2 = (ab)(ab) = a(ba)b = a^2b^2 Now, let's bring in the inverses:

a^-1 a (ba) b b^-1 = ba = a^-1 a^2 b^2 b^-1 = ab QED

2007-02-02 17:05:18 · answer #2 · answered by Scythian1950 7 · 1 0

fedest.com, questions and answers